Performance evaluation of stationary and semi-stationary acquisition with a non-stationary small animal multi-pinhole SPECT system. - Lange, Catharina; Apostolova, Ivayla; Lukas, Mathias; Huang, Kai P; Hofheinz, Frank; Gregor-Mamoudou, Betina; Brenner, Winfried; Buchert, Ralph (Molecular Imaging & Biology, 2014)
Purpose: Step-and-shoot mode with many angular steps results in long frame duration limiting the capability of single-photon emission computed tomography (SPECT) for fast dynamic scans. The present study evaluates acquisition with reduced angular sampling for fast imaging in preclinical research with the nanoSPECT/CTplus four-head multi-pinhole system.Procedures: Measurements with line sources, homogeneity phantoms and a Jaszczak phantom filled with (99m)Tc or (123)I were performed to evaluate the 'stationary' and 'semi-stationary' acquisition mode (one or two detector positions, respectively) with respect to spatial resolution, quantification, noise properties and image artefacts. An in vivo mouse study was performed with (99m)Tc-MAG3.Results: The fast acquisition modes resulted in only minor degradation of spatial resolution and quantification accuracy. Statistical noise in reconstructed images was significantly reduced compared to conventional SPECT, particularly at low count statistics. Stationary acquisition resulted in streak artefacts and spatial distortion.Conclusions: The semi-stationary acquisition mode of the nanoSPECT/CTplus allows fast dynamic SPECT with tolerable loss of image quality.